PELAKSANAAN PEMBINAAN TERHADAP NARAPIDANA WANITA DI LEMBAGA PEMASYARAKATAN KELAS IIA BANGKINANG BERDASARKAN PERATURAN PEMERINTAH NOMOR 31 TAHUN 1999 TENTANG PEMBINAAN DAN PEMBIMBINGAN WARGA BINAAN PEMASYARAKATAN - Hasanah, Uswatun; Firmanto, Fakhry; Maimory, Aminoel Akbar Novi (Jurnal Pahlawan, 2023)
A prisoner is someone who is considered guilty of his actions or deeds and has obtained a court deucision that has permanent legal force so that it can be said to have become a convict or convict, which will then serve his sentence in a detention room or also called a correctional institution. Penitentiary is an institution that aims to provide guidance to convicts, including female convicts. However, there are problems in coaching and mentoring for female convicts in class IIA Bangkinang penitentiary, that coaching and mentoring for female convicts in class IIA Bangkinang penitentiary has not been fully implemented, so this is not in accordance with Law Number 12 of 1995 concerning Corrections and Government Regulation Number 31 of 1999 concerning Guidance and Guidance of Correctional Inmates. The formulation of the problem in this study is how to implement the guidance of female convicts in the Bangkinang class II A penitentiary, what are the obstacles in implementing the guidance of female convicts in the Bangkinang class IIA penitentiary, and how to resolve the implementation of coaching for female convicts in the Bangkinang prison. prison class IIA Bangkinang. This research is a sociological law research, because the type of data used is primary data obtained from informants by interviewing the class IIA Bangkinang prison and questionnaires from female convicts, then secondary data is obtained from library materials and regulations related to the thesis title. . The first result of the research is that the implementation of training for female convicts in class IIA Bangkinang penitentiary has not been fully implemented because the female convicts are only given self-reliance coaching, namely making fish meatballs, fish floss and sweet martabak, while for personality coaching only legal awareness coaching, namely counseling from the Office Kampar Narcotics Agency. The second is that in carrying out coaching for female convicts in the Class IIA Bangkinang penitentiary, there are several obstacles, namely limited female employees, an unstructured location specifically for female convicts, lack of facilities and infrastructure, and no special supervisor from outside the penitentiary.